Incarcerating at Any Cost: Drug Trafficking and Imprisonment in Brazilian Court Reasoning - Maíra Rocha Machado; Mariana Celano de Souza Amaral; Matheus de Barros; Ana Clara Klink de Melo (Journal of Illicit Economies and Development, 2019)
Brazil has the third largest prison population worldwide—over 700,000 people. At least 28% of them are in prison for drug trafficking. Given that situation, this paper explores the conflicts among the law; the Supremo Tribunal Federal, or Brazilian Federal Supreme Court (STF) and lower court precedents. Based on a qualitative and quantitative study of Tribunal de Justiça de São Paulo, or São Paulo State Supreme Court (TJSP) and Superior Tribunal de Justiça, or Brazilian Superior Court of Justice (STJ) decisions between 2017 and 2018, this paper focuses on the arguments put forward by those courts to prevent the imposition of non-custodial sanctions on people convicted of drug trafficking even though they may be first-time offenders with no criminal record. Our research shows the main arguments used are related to the amount, type and variety of seized drugs; the convict’s criminal history; the person’s employment status at the time of arrest and the insufficiency of non-custodial sentences in cases of drug trafficking. Our conclusion is that the reasoning behind convictions for drug trafficking favors imprisonment even in situations in which the law and the STF precedents would allow non-custodial sentences.   Com mais de 700 mil pessoas presas, o Brasil ocupa o terceiro lugar no ranking dos países que mais encarceram. Desse total, ao menos 28% estão presas  por tráfico de drogas. Diante desse quadro, este texto explora as disputas que se estabelecem entre a lei, o Supremo Tribunal Federal (STF) e a jurisprudência dos tribunais inferiores. A partir de estudo qualitativo e quantitativo de decisões do Tribunal de Justiça de São Paulo (TJSP) e do Superior Tribunal de Justiça (STJ) de 2017 e 2018, este texto revela os argumentos construídos judicialmente para impedir a aplicação de sanções não prisionais a pessoas condenadas por tráfico, mesmo quando primárias e consideradas com bons antecedentes. De acordo com a pesquisa, os principais argumentos utilizados dizem respeito à quantidade, qualidade e diversidade de drogas aprendidas, a passagem anterior da pessoa condenada pelo sistema de justiça, a situação laboral da pessoa no momento de sua prisão e, ainda, à insuficiência da pena não prisional em caso de tráfico. O texto conclui que a fundamentação das sentenças condenatórias em casos de tráfico favorece a aplicação da pena de prisão, mesmo em situações nas quais o arranjo normativo e a jurisprudência do STF permitiriam decisões desencarceradoras.    Publisher's Note: This article has been published in both Portuguese and English. To download the Portuguese version, click the "Download" link and select "PDF (PT)".   Este artigo foi publicado tanto em Inglês, como em Português. Para baixar a versão em Português, clique "Download" e depois selecione "PDF (PT)".